Is Six Sigma an Appropriate Approach to Evaluate Performance of Testing Laboratories? - Pranil V. Sawalakhe; Nitin P. Gudadhe (Advanced Aspects of Engineering Research Vol. 8, 2021)
Six Sigma is a universal management approach implemented to companies like Motorola and General Electric. Acknowledging grand success in terms of global profitability and customer satisfaction in corporate world, Health care sector can also be benefited by the application of the same to achieve similar benefits in healthcare sector; Six Sigma is currently being spread in several laboratories around the world. Acknowledging this situation, few articles have been published in the peer-reviewed literature on this subject. The aim of this article is to clearly focus on different features of Six Sigma and its successful applications in testing laboratories, as well as to systematically review articles and books discussing Six Sigma strategy implementation in the laboratory field.